Impacto de la calidad del servicio eléctrico en la recaudación por venta de energía eléctrica en Electro Oriente S.A. - Iquitos periodo 2017 - 2021 - Damián Martínez, Henry Manolo (2022)
The quality of the service of the company Electro Oriente S.A. it is measured through the quality of the supply and the quality of the product. This doctoral thesis is carried out to determine the impact of the quality of electrical service on the collection for the sale of electrical energy in Electro Oriente S.A.- Iquitos in the period 2017 - 2021. Taking this into account, the present Quantitative type research, Correlational level and Non-Experimental design was carried out. The investigation concludes that the quality of the electrical service has no impact on the collection for the sale of electrical energy of the company Electro Oriente S.A., during the period 2017 - 2018, based on the results of the statistical test that has a Correlation Coefficient of r = -0.225228679; and a Determination Coefficient of R2 = 0.050727958; both values being below the minimum accepted for a good statistical association. Similarly, the quality of the electricity supply has no influence on the collection from the sale of Electro Oriente S.A., in the same period, based on the results of the Correlation Coefficient r = -0.230857816; and the Coefficient of Determination of R2 = 0.053295331. The quality of the product does not influence the collection either, since a Correlation Coefficient of r = 0.120410183 was obtained; and a Coefficient of Determination of R2 = 0.014498612. The collection rate is 70.98%.